Alumina-supported cadmium sulfide photocatalysts for hydrogen production from water: Role of dissolved ammonia in the impregnating solution - Arora M.K.; Sahu N.; Upadhyay S.N.; Sinha A.S.K. (My University, 2025)
Alumina-supported cadmium sulfide photocatalysts were prepared for the photocatalytic reduction of water to hydrogen using visible light. The activity depends on the loading of CdS in catalysts and on the solution used for the impregnation of alumina for catalyst preparation. The catalysts were characterized by X-ray diffraction and X-ray photoelectron spectroscopy. Those catalysts, which had CdS in crystalline form and preferentially distributed on the surface, showed better activity. The crystallinity of CdS was related to the loading of CdS in the catalyst. The use of an ammoniacal impregnating solution resulted in a preferential distribution of CdS on the surface of alumina. The possible role of ammonia in causing the solute segregation to the surface during the drying stage of the catalyst preparation has been explained.